Liquid phase exfoliation and characterisation of novel layered materials - Harvey, Andrew (Trinity College (Dublin, Ireland). School of Physics, 2017)
Over the last decade, there has been a large push towards making two dimensional (2D) nanomaterials a more realistic component of industrial applications. One of the main limiting factors to this point has been the ability to produce these materials in large quantities. In 2008, it was demonstrated by Coleman et al that liquid phase exfoliation (LPE) could be utilised as a production method of large quantities of 2D nanosheets. This method was first performed on graphene and transition metal dichalcogenides, such as M0S2 and WS2. A recent move has been to try to exfoliate new materials such as molybdenum trioxide and black phosphorus but the extension to newer materials has been slow. Presented in this thesis is the continuation of this via the exfoliation of novel layered materials, such as gallium sulphide (GaS) and layered double hydroxides (LDHs). Initially this technique was applied to GaS where the production of large quantities of nanosheets by liquid exfoliation of layered GaS powder was demonstrated
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017